2018
DOI: 10.3389/fphar.2018.00534
|View full text |Cite
|
Sign up to set email alerts
|

Fast Green FCF Alleviates Pain Hypersensitivity and Down-Regulates the Levels of Spinal P2X4 Expression and Pro-inflammatory Cytokines in a Rodent Inflammatory Pain Model

Abstract: Fast Green FCF (FGF), a biocompatible dye, recently drew attention as a potential drug to treat amyloid-deposit diseases due to its effects against amyloid fibrillogenesis in vitro and a high degree of safety. However, its role in inflammatory pain is unknown. Our study aimed to investigate the effect of FGF in the inflammatory pain model induced by complete Freund’s adjuvant (CFA) and to identify the associated mechanisms. We found that systemic administration of FGF reversed mechanical and thermal pain hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 49 publications
3
11
0
Order By: Relevance
“…According to our previous study, we found that the anti-nociceptive effect of Fast green FCF was accumulative and a single Fast green FCF application did not reduce inflammatory pain. In addition, systemic administration of 100 mg/kg Fast green FCF had a more rapid and significant effect than 30 mg/kg Fast green FCF on inflammatory pain, and the anti-nociceptive effect of 100 mg/kg Fast green FCF persisted after the discontinuation of daily treatment (Xu et al, 2018). Therefore, we here investigated the anti-depressive effect of 100 mg/kg Fast green FCF administration (daily for 7 days, before LPS injection) on LPS-treated mice because LPS-induced depression-like behaviors occurred at 24 h after LPS treatment.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…According to our previous study, we found that the anti-nociceptive effect of Fast green FCF was accumulative and a single Fast green FCF application did not reduce inflammatory pain. In addition, systemic administration of 100 mg/kg Fast green FCF had a more rapid and significant effect than 30 mg/kg Fast green FCF on inflammatory pain, and the anti-nociceptive effect of 100 mg/kg Fast green FCF persisted after the discontinuation of daily treatment (Xu et al, 2018). Therefore, we here investigated the anti-depressive effect of 100 mg/kg Fast green FCF administration (daily for 7 days, before LPS injection) on LPS-treated mice because LPS-induced depression-like behaviors occurred at 24 h after LPS treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous investigation suggests the relationship between Fast green FCF’s anti-nociceptive action and the downregulation of spinal P2X4R expression in CFA-induced inflammatory pain (Xu et al, 2018). Furthermore, some studies show that P2X4R is abundantly expressed in glial cells of the hippocampus and LPS facilitates P2X4R-mediated inward currents (Stokes et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations